2019
DOI: 10.1177/2331216519877301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Noise Exposure on Proxy Measures of Cochlear Synaptopathy

Abstract: Although there is strong histological evidence for age-related synaptopathy in humans, evidence for the existence of noise-induced cochlear synaptopathy in humans is inconclusive. Here, we sought to evaluate the relative contributions of age and noise exposure to cochlear synaptopathy using a series of electrophysiological and behavioral measures. We extended an existing cohort by including 33 adults in the age range 37 to 60, resulting in a total of 156 participants, with the additional older participants res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
99
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(115 citation statements)
references
References 45 publications
(120 reference statements)
10
99
3
3
Order By: Relevance
“…This was true for all the conditions tested (two carrier frequencies, two modulation rates, in quiet and in noise). The absence of age effects on sensitivity to envITDs was also reported by Prendergast et al (2019), despite the fact that Prendergast et al (2019) used a higher modulation rate (255 Hz),…”
Section: Interaural Time Difference In Stimulus Envelopementioning
confidence: 53%
See 4 more Smart Citations
“…This was true for all the conditions tested (two carrier frequencies, two modulation rates, in quiet and in noise). The absence of age effects on sensitivity to envITDs was also reported by Prendergast et al (2019), despite the fact that Prendergast et al (2019) used a higher modulation rate (255 Hz),…”
Section: Interaural Time Difference In Stimulus Envelopementioning
confidence: 53%
“…These agerelated deficits were observed for high (≥ ~100 Hz) but not for lower modulation rates (Grose et al, 2009;Purcell et al, 2004). Measures of temporal envelope processing are often significantly correlated with hearing sensitivity (e.g., Grose et al, 2009;Prendergast et al, 2019;Purcell et al, 2004) suggesting that some of the reported age effects may have been related to deficits in cochlear function rather than aging per se.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations